(untitled) (Palíndromo, 2019)
The text deals with contemporary art in the classroom, through proposals developed in two education networks, one at the state level and another at the federal level. The work exposes research elaborated by art teachers, who have in contemporary art their motto of research. The paper presents considerations about the context of the classroom in which contemporary art makes itself present in its availability to deal with daily life, as in Certeau (2009), contemplating a guidance for to the sight of the form treated by Didi-Huberman (1998).